Realities of leprosy control: updating scenarios - Aguinaldo Gonçalves (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2013)
In the light of successive therapeutical difficulties for leprosy control, the application of drug therapy combination over the last decades has brought about an expectation of cure for leprosy patients and also for the elimination of this illness as a Public Health problem. However, there has been a progressive reduction in the prevalence of leprosy, but without any apparent impact on transmission, which has led to recognized need for solid assessment of respective epidemiological evidence as grounds for interventions to solve the problem. In this regard, here we present a retroanalytical qualitative and quantitative study, combined with a prospective diachronic approach, based on the association of documental review techniques and analysis of content, involving the following phases in succession: assembly of an operational scheme, execution of search strategy, application of criteria, selection of studies, data extraction and processing, implementation of analysis plan and preparation of final text. The appropriate execution of the procedures, as applied, allows us to obtain and discuss the identification of three main scenarios: the elimination of the illness as a public health problem (Neglected Illness); therapeutic aspects (Resistance; Relapse; Non-Adherence; Persistence) and complexity (complications and physical incapacities). The conclusions that have been reached indicate,mainly, that the reality of leprosy control with the use of combination drug therapy, still needs to be handled with care, even more so as this is just a fragment of the set of people once under medical attention, which also correspond to a parcel of the set of people affected by the ailment.